The effect of concurrent task difficulty on working memory during simulated driving - RADEBORG, KARL; BRIEM, VALDIMAR; HEDMAN, LEIF R. (Ergonomics, 1999)
The effects of a concurrent simulated driving task on performance in a working memory task was investigated in 20 subjects (10 females, 10 males, median age = 33 years). The working memory task consisted of (1) judging whether simple sentences, presented in series of four, were meaningful, and (2) recalling the first words of each sentence in the series. The concurrent task had three levels of difficulty: (a) no driving, (b) easy driving, and (c) difficult driving. Being involved in the driving task (levels b and c) was found to be associated with significant deterioration of both recall and judgement, but whether the driving task was easy or difficult (level b or c) had no discernible effect on either recall or judgement. The results are discussed with reference to models of working memory and attention.